ANALYSIS OF THE EFFECT OF WORK FROM HOME ON EMPLOYEE PRODUCTIVITY DURING THE COVID-19 PANDEMIC - I Gede Putu Kawiana (Jurnal Ekonomi, 2021)
The Covid-19 pandemic has had a significant impact on various aspects of life, including the world of work. Implementing a work from home (WFH) policy is one of the solutions that many companies take to maintain the health and safety of their employees. However, the impact of this transition on employee productivity is still being debated. This study aims to analyze the effect of implementing work from home on employee productivity during the Covid-19 pandemic. This study uses a quantitative approach with a verification approach by taking a sample of 113 employees who work from home . The results of the study show that WFH has a positive and significant impact on their productivity levels. This is reinforced by the hypothesis test which shows that the calculated t value is greater than the t table value (4.755 > 1.662), and the significance value is much smaller than the predetermined standard (0.000 <0.05). The WFH variable has an influence on employee productivity by 16.7 percent while the remaining 83.3 percent is influenced by other factors not examined in this study.